Analysis of the effect of sterilization and storage on the quality of Pinus yunnanensis pollen based on untargeted metabonomics. Issue 12 (16th October 2021) - Mei, Suhuan; Yang, Changjun; Song, Xiao; Wang, Tong; Wang, Yali; Geng, Yue; Wang, Jun; Su, Shufang
Abstract: Pinus yunnanensis pollen has many bioactivity compounds. However, the effect of sterilization and storage on the quality of pine pollen remains unknown. In this study, 36 metabolites, including kaempferol, cetyl betaine, methyl ricinoleate, and naringenin, were tentatively identified in fresh pine pollen (YNS), irradiation sterilized pine pollen (IR), ultra‐high temperature instantaneous sterilized pine pollen (UHT), one‐year pine pollen (OY) and two‐year pine pollen (TY) using untargeted metabolomics based on ultra‐high performance liquid chromatography tandem mass spectrometry. Compared with UHT, IR had less effect on pine pollen, and the longer of storage time, the greater effect on pine pollen metabolites. YNS contain more kaempferol and N‐(2‐hydroxypropyl) methacrylamide, which indicated that they were easily lost during the storage and sterilization. And the other four groups all contained 2‐formylpyridine which might be due to contamination during sterilization and storage. Practical applications: Metabolomic has been widely used in food research and quality control. The result showed that kaempferol, cetyl betaine, methyl ricinoleate, and naringenin were greatly affected by processing methods, which provided a reference for the storage and sterilization of pine pollen. Additionally, this study supplied application prospects for pine pollen research and quality control in other natural product.